Statistical modelling of a terrorist network. (18th September 2016) - Aitkin, Murray; Vu, Duy; Francis, Brian
Summary: The paper investigates the group structure in a terrorist network through the latent class model and a Bayesian model comparison method for the number of latent classes. The analysis of the terrorist network is sensitive to the model specification. Under one model it clearly identifies a group containing the leaders and organizers, and the group structure suggests a hierarchy of leaders, trainers and 'foot soldiers' who carry out the attacks.